Compatibility of slideway oils with water soluble metal working fluids - Marica Dugić; Branko Despotović; Novak Damjanović; Pero Dugić (Journal of Engineering & Processing Management, 2017)
Slideway oils have application in many industries, such as automotive, food, beverage, packaging, and considerable amount is used in small machinery workshops. Market analyses have shown that most common viscosity grade is ISO VG 68, followed by ISO VG 220. Because water soluble metal working fluids come in contact with slideway oils, purpose of this research was to test the influence of water soluble fluids on most commonly used viscocity grades of slideway oils. Compatibility of slideway oils with water soluble metal working fluids is very important for effective funcioning of slideway machines, and for life span of slideway oil itself. Compatibility was tested with specially adjusted demulsivity tests, regarding the capability of separating specific amount of water soluble metal working flud from slideway oil. Different formulations of cooling and lubricating fluid and slideway oil give different times and ratios of separated oil and water on modified test. Test results can be used in development of new formulations of these products, and with selection of emulsifying fluids for metal working and oils for slideways for some applications.
Keywords: compatibility; demulsivity; slideway oils; water soluble metal working fluids